Effect of auditors' independence on financial reporting quality of Nigerian deposit money bank - Abdul-Ganiyy Agbaje; Raji Sadiq; Oke Adesoji; Shittu Aminat Oyindamola (Financial Internet Quarterly, 2021)
This study examined the effect of auditor independence on financial reporting quality of deposit money banks in Nigeria with Financial Reporting Quality as the dependent variable; Audit Fee, Audit Firm Size and Audit Meeting as independent variables, Debt Ratio as control variable. The sample period covered six (6) years (2013 to 2018) and data were extracted from the audited annual reports of ten (10) selected deposit money banks. The results of this study revealed that Audit Fee, Audit Meeting and Debt Ratio are positive but have insignificant impact on financial reporting quality; Audit Firm Size is negative and has insignificant impact on financial reporting quality. The study recommends orientation and reorientation of audit committee members to guarantee significant influences on financial reporting quality.
Keywords: E4; E5; E6; 330; audit independence; audit fee; audit meeting; financial reporting quality